Effect of biotin supplementation on neuropathic pain induced by chronic constriction of the sciatic nerve in the rat - Ali-Reza Abed; Alireza Abed; Hamid Reza Banafshe; Ebadallah Shiri Malekabad; Sattar Gorgani-firuzjaee; Ali-Reza Dadashi (Wolters Kluwer Medknow Publications, 2021)
Background and purpose: Neuropathic pain is one of the most common types of chronic pain that is very difficult to treat. Numerous studies have shown the potential role of vitamins in relieving both hyperalgesia and allodynia. Based on the convincing evidence, this study was designed to evaluate the possible antinociceptive effect of biotin on neuropathic pain in rats. Experimental approach: This study was performed on male Sprague Dawley rats weighing 200-300 g. Neuropathic pain was induced by tying the sciatic nerve. Chronic constriction injury (CCI) of the sciatic nerve resulted in hyperalgesia and allodynia. To measure the thermal hyperalgesia, the plantar test was used. Also to evaluate the cold and mechanical allodynia, acetone test and von Frey test were applied. Biotin (4, 8, and 16 mg/kg) was administered orally as two different treatment regimens, acute and chronic. Findings/Results: Acute oral administration of biotin (4, 8, and 16 mg/kg p.o.) on the 7th, 14th, and 21st postoperative days couldn't reduce pain sensitivity compared to the CCI group. However, following the oral administration of biotin (8 and 16 mg/kg p.o.) from the first day after the surgery until day 21, mechanical allodynia (P < 0.001) and heat hyperalgesia (P < 0.05) significantly relieved. Conclusion and implications: Our results suggest that biotin can be considered as a potential therapeutic for the treatment of neuropathic pain, and supplementation with this vitamin could reduce the required doses of analgesic drugs. However, further studies are needed to confirm this hypothesis.